Evaluation of Development Policy through Water Environmental Carrying Capacity Analysis in North Kendeng Mountain, Indonesia - Sudharto Prawata Hadi; Hartuti Purnaweni; Bulan Prabawani; Rizkiana Sidqiyatul Hamdani (Indonesian Journal of Geography, 2023)
North Kendeng Mountain has abundant limestone that can potentially be utilized for cement material, cosmetics, paint, and other commercial products. This area also provides water resource storage widely utilized for household use and crop irrigation for local people. This condition has sparked conflict between the government and investors on one side with local people and academicians on the other side. The government and investors, prefer this area for commercial uses while the cons prefer for conservation area. The Strategic Environmental Assessment (SEA) for the North Kendeng ecosystem found that spatial planning and mid-term development planning by the provincial government and related regency governments are oriented toward natural resources utilization and prioritize the area for mining. This paper analyses water environmental carrying capacity implications if the government’s policy and planning are implemented. The type of research is descriptive analysis. The data collection techniques include informal interviews, observation, and literature review. The qualitative data on the development policies are analyzed with content analysis technique including descriptive, interpretative, and explanative. The comparison analysis also conducted to understand the interaction between proposed development activities and the existing environmental condition based on water environmental carrying capacity (WECC) result, and to analyze policy orientation on North Kendeng Mountain Area. After comparing the water demand and availabilityboth with and without government’s policy, this study found that condition of water environmental carrying capacity comparing the demand and availability both with and without policy and planning are deficit for all regencies, except Lamongan regency. This development policy potentially worsens water deficit for all regencies. Therefore, it is suggested that revising the policy and updating the planning are required to achieve sustainable utilization of the North Kendeng Mountain Area.